2018
DOI: 10.1002/jez.b.22813
|View full text |Cite
|
Sign up to set email alerts
|

Massive parallel expansions of Methuselah/Methuselah‐like receptors in schizophoran Diptera

Abstract: The Methuselah/Methuselah-like (Mth/Mthl) family of G-protein coupled receptors (GPCRs) is represented by 16 homologs in the fruit fly Drosophila melanogaster. Three of them have thus far been functionally characterized and found to play critical roles in cell adhesion, immunity, lifespan, and oxidative stress regulation. Evolutionary studies have shown that the large number of D. melanogaster Mth/Mthl GPCRs arose by at least two rounds of gene duplications. The first produced the "mth superclade" subfamily an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The Mth/Mthl gene family arose in early metazoans and, as evolution progressed, underwent numerous extinction and expansion events that made it abundant in insects but absent in vertebrates (Patel et al 2012 ; de Mendoza et al 2016 ; Friedrich et al 2018 ). Phylogenetic analyzes of Mth protein have shown that it has undergone an unusually high level of adaptive amino acid divergence concentrated in the intra- and extracellular loop domains as an evolutionary strategy in a signal transduction pathway that can modulate lifespan in nature (Schmidt et al 2000 ).…”
Section: Gpcr Influencing Lifespanmentioning
confidence: 99%
“…The Mth/Mthl gene family arose in early metazoans and, as evolution progressed, underwent numerous extinction and expansion events that made it abundant in insects but absent in vertebrates (Patel et al 2012 ; de Mendoza et al 2016 ; Friedrich et al 2018 ). Phylogenetic analyzes of Mth protein have shown that it has undergone an unusually high level of adaptive amino acid divergence concentrated in the intra- and extracellular loop domains as an evolutionary strategy in a signal transduction pathway that can modulate lifespan in nature (Schmidt et al 2000 ).…”
Section: Gpcr Influencing Lifespanmentioning
confidence: 99%